EFFECT OF PLANT COVERAGE ON MINERALOGICAL CHANGES OF MICA IN RHIZOSPHERE - & Essa, Al- Jaff (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Three soil sites were chosen in sulaymaniyah governorate, for three types of trees (pine, oak  and pear), in order to study the effect of biochemical activities in rhizosphere on weathering of mica and potassium availability comparing with Bulk soil. Results of X-ray showed that the transformation process of mica to 2:1 expandable minerals in rhizosphere was exceeded than in Bulk soil of all type of trees. While the superiority of mica weathering, and increase of smectite content in all rhizosphere were taken a followed sequence. Pine > oak > pear. Results of SEM for clay samples of Bulk soil showed there was no cracks, splitting, Exfoliation, and no separation of the layers on the surfaces of minerals. While the inspection results confirmed two types of mica edges weathering: first, was a complete edge weathering of mica in Bulk soil of pine trees, and second, was un completed edge weathering in Bulk soil of oak and pear. Also a complete pal colour of mica particle surfaces were found in clay samples of  rhizosphere soil under pine trees. While the surfaces and edges of mica were less affected by the weathering processes, was found in clay samples of rhizosphere  soil of oke and pear trees.